Governments, farmers and seeds in a changing Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Governments, farmers and seeds in a changing Africa by Elizabeth Cromwell 1996 176pp price UKL30 00 ISBN 085198 976 4